The impact of childhood trauma on borderline personality organization in a community sample of Greek emerging adults - Malafanti, A; Yotsidi, V; Sideridis, G.; Giannouli, E; E P Galanaki; Malogiannis, I (Acta Psychologica, 2024)
There is limited research on the role of childhood trauma in personality pathology according to Kernberg’s psychodynamic model of internalized object relations. Because childhood trauma reflects the disruptions of these relations, it is expected to predict borderline personality organization, especially at the threshold of adulthood. Therefore, the main aim of this retrospective study was to examine the impact of childhood trauma on borderline personality organization in a community sample of emerging adults. Participants were 543 Greek individuals aged 18-29 (M = 21.45; 58.6% females; 85.1% university students). They completed the Greek versions of the Traumatic Antecedents Questionnaire (TAQ) and the Inventory of Personality Organization (IPO), which were tested for their factorial structure, reliability, and measurement invariance across gender, as few empirical data exist on the psychometric properties of these measures. Confirmatory factor analyses showed that the TAQ consisted of four factors, namely positive experiences, abuse, traumatic life events, and family chaos. The five-factor theoretical structure of the IPO, namely primitive defenses, identity diffusion, reality testing, aggression, and moral values, was confirmed. Low to moderate links between childhood trauma and borderline personality organization were found, with stronger links emerging for abuse and family chaos. Structural equation modeling showed that the various forms of childhood trauma across the age periods studied (i.e., 0-6, 7-12, 13-18) significantly and differentially predicted the dimensions of borderline personality organization. The finding that stronger links emerged when trauma occurred in older ages may be attributed to the retrospective method of the study. Gender differences were also found; for example, personality pathology was more likely in men when abuse and traumatic life events occurred in younger ages and abuse was a more important risk factor for personality pathology in women. This study highlights the impact of childhood adversity on personality pathology in emerging adulthood, provides empirical support for Kernberg’s psychodynamic model, and has useful implications for trauma-informed early screening, prevention, and intervention regarding personality pathology in young people. Limitations of this study and suggestions for future research are outlined.